Soil Bacterial Diversity and Its Relationship with Soil CO2 and Mineral Composition: A Case Study of the Laiwu Experimental Site - Zhang, Hongying; Gao, Zongjun; Shi, Mengjie; Fang, Shaoyan (International journal of environmental research and public health, 2020)
To better understand the characteristics of soil bacterial diversity in different environments, the Laiwu Qilongwan experimental site was selected as it is of great significance for the study of geochemical cycles. The soil CO2, mineral composition and bacterial community were analyzed by an EGM-4 portable environmental gas detector, an X-ray diffractometer and 16S rDNA high-throughput sequencing, and soil bacterial diversity and the relationship between soil bacterial diversity and environmental factors were studied. The results showed that with increasing soil depth, the CO2 content increased, the feldspar and amphibole contents increased, the quartz content decreased, the richness of the soil bacterial community increased, the relative richness of Nitrospirae increased, and Chloroflexi decreased. The dominant bacteria were Proteobacteria, Actinobacteria and Acidobacteria. There were slight differences in soil CO2, mineral composition and dominant bacterial flora at the same depth. Actinobacteria, Proteobacteria and Firmicutes were the dominant phyla of L02. The CO2 was lowest in bare land, and the quartz and K-feldspar contents were the highest. Soil CO2 mainly affected the deep bacterial diversity, while shallow soil bacteria were mainly affected by mineral components (quartz and K-feldspar). At the same depth, amphibole and clay minerals had obvious effects on the bacterial community, while CO2 had obvious effects on subdominant bacteria.